2014
DOI: 10.1080/1331677x.2014.947107
|View full text |Cite
|
Sign up to set email alerts
|

Does banking sector development promote economic growth? An empirical analysis for selected countries in Central and South Eastern Europe

Abstract: Economic growth is one of the ultimate goals of any economic system. This article examines the question whether in 16 transition economies from Central and South Eastern Europe the banking sector influences economic growth. The empirical investigation was carried out using a generalised method of moments (GMM) dynamic panel method. We measure the development in the banking sector using the bank credit to the private sector, interest rates, and ratio of quasi money (RQM). The research results show that credit t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 42 publications
3
82
1
Order By: Relevance
“…An overall weak relationship between bank development and growth in nine EU accession countries in 1996-2000 was found by [27] and no impact of stock market development on growth. Similarly, the weakness of the link for 16 CESEE countries during the 1991-2011 period was confirmed by [28], and was explained mainly by the high stock of NPL and banking crisis experiences. In the same vein, evidence by [29], focusing on 10 new European Union members in 1994-2007, suggested that the stock and credit markets in these economies are still underdeveloped and that their contribution to economic growth is limited, owing to low financial depth.…”
Section: Literature Reviewmentioning
confidence: 84%
“…An overall weak relationship between bank development and growth in nine EU accession countries in 1996-2000 was found by [27] and no impact of stock market development on growth. Similarly, the weakness of the link for 16 CESEE countries during the 1991-2011 period was confirmed by [28], and was explained mainly by the high stock of NPL and banking crisis experiences. In the same vein, evidence by [29], focusing on 10 new European Union members in 1994-2007, suggested that the stock and credit markets in these economies are still underdeveloped and that their contribution to economic growth is limited, owing to low financial depth.…”
Section: Literature Reviewmentioning
confidence: 84%
“…For example, by investigating 21 African countries, Ozturk and Acaravci (2013) reveals that financial development has limited effect on economic growth for most of the countries. Addition to that, Petkovski and Kjosevski (2014) examines Central and South Eastern European countries by utilizing GMM dynamic panel model for ratio of bank credits in private sector, interest rates and Ratio of Quasi Money (RQM). They find evidence of Ratio of Quasi Money (RQM), a proxy of financial, openness impact on economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, Fink et al [2008] found in 9 EU accession countries over 1996-2000 an overall weak relationship and no impact of stock market development on growth. Similarly, Petkovski and Kjosevski [2014], for panel data in 16 CESEE countries, over the period of 1991-2011, confirmed the weaknesses of the link, which is mainly due to the high level of NPLs and banking crisis experiences (mostly in mid 90s). Using longer panel data for 27 transition economies over the period of 1989-2004Akimov et al [2009 found contrasting evidence -there was a strong and positive link between financial development and economic growth.…”
Section: Review Of Literaturementioning
confidence: 65%